2010
DOI: 10.1111/j.1745-7599.2010.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioners’ job satisfaction and intent to leave current positions, the nursing profession, and the nurse practitioner role as a direct care provider

Abstract: This study will help bridge the gap in literature relating to NP job satisfaction, their intent to leave, and anticipated turnover. The results of this study could potentially assist employers in developing strategies for recruitment and long-term retention. These results may also give insight into how NPs can make their work environments more fulfilling. Additionally, these results may contribute to continued role adaption necessary for the constantly changing work environments in which NPs currently practice. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
116
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 43 publications
13
116
4
2
Order By: Relevance
“…The best way of anticipating actual nurses' turnover or attrition is their intent to leave or stay and job satisfaction [3][4][5]21,23,25]. Results of previously mentioned studies were similar to the findings from this study which support that, nurses intend to leave when they are less satisfied, and intend to stay when they are more satisfied.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The best way of anticipating actual nurses' turnover or attrition is their intent to leave or stay and job satisfaction [3][4][5]21,23,25]. Results of previously mentioned studies were similar to the findings from this study which support that, nurses intend to leave when they are less satisfied, and intend to stay when they are more satisfied.…”
Section: Discussionsupporting
confidence: 81%
“…The demographic characteristics were found to have a significant effect on the nurses' satisfaction and their plans to stay or to leave the job [25]. On the contrary, other study has found no correlation between job satisfaction and demographic characteristics [7].…”
Section: Discussionmentioning
confidence: 61%
“…Ha hecho posible cuantificar el rendimiento de la actividad asistencial a través de los cuadros de mando, creando una cultura de evaluación y de calidad ética 10 . Por su estilo de dirección favorece el suministro de cuidados de alta calidad a bajo coste elevando la satisfacción de los pacientes 11 . Todos estos aspectos, derivan en relaciones profesionales más autónomas, elemento que ha demostrado ser clave en el proceso de adaptación y consolidación de un modelo de gestión funcional 2,12 .…”
Section: Introductionunclassified
“…Conversely, quality patient contact and teamwork (Moyle et al, 2003), social support and empowerment (Joiner et al, 2004), and investment in learning and development (Johnson et al, 2011) , have all been shown to correlate positively with job satisfaction. High satisfaction correlates with a decreased intention to leave the workplace (De Milt et al, 2011).…”
Section: Stress In the Working Environmentmentioning
confidence: 99%
“…Quality patient contact and teamwork (Moyle et al, 2003), social support and empowerment (Joiner, Stanton, & Bartram, 2004), and investment in learning and development (Johnson, Hong, Groth & Parker, 2011), have all been shown to relate positively with job satisfaction. High satisfaction correlates with a decreased intention to leave the workplace (De Milt, Fitzpatrick, & McNulty, 2011). Stress (Coomber & Barriball, 2006), stress resiliency (Larrabee et al, 2010), perceptions of the adequacy of staffing and missed nursing care (Kalisch, Tschanen, & Lee, 2011), and issues around professional status, remuneration and autonomy (Cowin, 2002), have all been identified as contributing to decreased job satisfaction, and may lead to turnover (Coomber & Barriball, 2006).…”
Section: Job Satisfactionmentioning
confidence: 99%